Effects of Availability, Contingency, and Formulaicity on the Accuracy of English Grammatical Morphemes in Second Language Writing. Issue 4 (25th April 2022) - Murakami, Akira; Ellis, Nick C.
Abstract: We investigated whether the accuracy of grammatical morphemes in second language (L2) learners' writing is associated with usage‐based distributional factors. Specifically, we examined whether the accuracy of L2 English inflectional morphemes is associated with the availability (i.e., token frequency) and contingency (i.e., token frequency relative to other forms with the same lemma) of the inflected word form as well as the formulaicity of the context in which it occurs (i.e., predictability of the form given the surrounding words). Data drawn from a large‐scale learner corpus indicated that contingency is a robust predictor of morpheme accuracy, thereby supporting the usage‐based view that language learners are sensitive to distributional properties in their input. Furthermore, the relationship of contingency with accuracy does not necessarily lessen when learners' proficiency rises. Contrary to previous research investigating online processing, we did not identify in our study availability and formulaicity as predictors of accuracy of morpheme production in writing. Abstract :